Gene delivery techniques for adult stem cell-based regenerative therapy. (November 2013) - Seo, Seog-Jin; Kim, Tae-Hyun; Choi, Seong-Jun; Park, Jeong-Hui; Wall, Ivan B; Kim, Hae-Won
Over the past decade, stem cells have been considered to be a promising resource to cure and regenerate damaged or diseased tissues with research extending from basic studies to clinical application. Furthermore, genetically modified stem cells have the potential to reduce tumorigenic risks and achieve safe tissue formation. Recent advances in genetic modification of stem cells have rendered these cells more accessible and stable. The successful genetic modification of stem cells relies heavily on designing vector systems, either viral or nonviral vectors, which can efficiently deliver therapeutic genes to the cells with minimum toxicity. Currently, viral vectors showing high transfection efficiencies still raise safety issues, whereas safer nonviral vectors exhibit extremely poor transfection in stem cells. Here, we attempt to review and discuss the main factors raising concern in previous reports, and devise strategies to solve the issues in gene delivery systems for successful stem cell-targeting regenerative therapy.